2003
DOI: 10.1017/s0014479703001431
|View full text |Cite
|
Sign up to set email alerts
|

Yield Responses of Winter (Rabi) Forage Crops to Irrigation With Saline Drainage Water

Abstract: A field experiment in an alluvial sandy loam saline soil was conducted during the winter (rabi ) season from 1997-98 to 1999-2000 at the Central Institute for Research on Buffaloes, Hisar, to study the effect of saline drainage water (EC = 3.6 -7.4) on five (rabi ) forage crops: oat (Avena sativa), rye grass (Lolium rigidum), senji (Indian clover) (Melilotus indica) berseem (Egyptian clover) (Trifolium alexandrinum) and shaftal (Persian clover) (Trifolium resupinatum). All the crops were established using can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Conjunctive use of saline and fresh water for irrigation allows the utilization of poor quality surface water and/or groundwater resources with freshwater (Rhoades, 1987;Sharma & Rao, 1998;Crescimanno et al, 2002;Datta & Jong, 2002;Yadav et al, 2004;Kaur et al, 2007). Blending and cyclic use are two options adopted when coordinating the use of water with different qualities (Rhoades et al, 1992;Wichelns et al, 2002;Hamilton et al, 2007;Dudley et al, 2008;Kulkarni, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Conjunctive use of saline and fresh water for irrigation allows the utilization of poor quality surface water and/or groundwater resources with freshwater (Rhoades, 1987;Sharma & Rao, 1998;Crescimanno et al, 2002;Datta & Jong, 2002;Yadav et al, 2004;Kaur et al, 2007). Blending and cyclic use are two options adopted when coordinating the use of water with different qualities (Rhoades et al, 1992;Wichelns et al, 2002;Hamilton et al, 2007;Dudley et al, 2008;Kulkarni, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The adverse impact of poor quality water use on soil health depends on soil texture and climatic conditions (Singh and Poonia, 1980). This adverse impact on soil health and crop production could be mitigated to some extent by conjunctive use of good and poor quality water in cyclic mode (Bradford and Letey, 1992;Yadav et al, 2004). Hence, the present investigation was carried out to quantify the impact of conjunctive use of saline water on different fodder production systems, their quality and certain physico-chemical properties of loamy-sand soils of semi-arid zone under monsoonal climate.…”
Section: Introductionmentioning
confidence: 99%
“…The mixing is possible in areas where good quality water can be made available in adequate quantities at the time of its requirement. Several researchers compared mixing and cyclic uses of two quality waters and concluded that higher irrigation efficiency can be achieved with cyclic use when good quality water is applied at the initial stages and poor quality water is used at the later stages when plants can tolerate the salts better (Bradford and Letey, 1992;Naresh et al, 1993;Yadav et al, 2004). The use of poor quality water for crop production in arid regions was reported by Ben-Gal et al (2009).…”
Section: Application Modesmentioning
confidence: 99%